A resilient temperature sensor system for power line monitoring in 65nm CMOS process - Maestro, Rico Jossel Mindoro; Alarcon, Louis P.; Hizon, John Richard E. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The temperature of power lines varies depending on the current flow and other environmental variables. It is an important factor that can be used to efficiently distribute the load on the power grid. Thus, a reliable temperature sensor should be incorporated in a sensor node that will be mounted on the power lines. However, to efficiently monitor the power distribution system, multiple nodes should be mounted on different parts of the grid. Therefore, this requires the nodes to be cheap in terms of both area and power. Also, to increase the scalability of the system to many nodes, sources of energy such as batteries should be removed. Instead, energy should be harvested from the environment. However, these factors and including the application of the node make it vulnerable to voltage, process and temperature variation, which introduce error that makes the sensors inaccurate. This thesis presents a design methodology considering the effects of process, voltage and temperature variation, therefore, reducing the error at the output of the sensor. The methodology was applied in the implementation of a temperature sensor system to obtain an acceptable accuracy with a 0.5V supply over the range of 0°C to 100°C and across process variation
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Wireless sensor nodes; Electric power distribution; Temperature sensor systems; Distributed temperature sensing